The relationship between nutrition and depression in the life process: A mini-review - Gülseren Nur Ekinci; Nevin Sanlier (Experimental Gerontology, 2023)
Depression is one of the leading health problems, and >300 million people have a major depressive disorder and this number is getting increasing. Depression complicates the management of existing chronic diseases and the management of complications that may arise. A person's mental state can affect their food preferences, and food preferences can also affect their mental state. In this paper, depression and eating behavior, diet quality, folic acid, vitamin B12, vitamin B6, vitamin D, omega-3 fatty acids, magnesium, selenium, zinc and copper, prebiotics and probiotics are discussed. Research on the subject emphasizes that diet quality may also affect the occurrence of depression. However, studies also indicated that dietary nutrients such as folic acid, vitamin B12, vitamin B6, omega-3 fatty acids, zinc, selenium, and magnesium might be associated with the risk of depression.